2001
DOI: 10.1007/s004260000054
|View full text |Cite
|
Sign up to set email alerts
|

Sequential analysis of a Simon task - evidence for an attention-shift account

Abstract: We investigated the attention-shift hypothesis of the Simon effect by analysing the effect of repeating relevant colour or irrelevant location of the stimulus in four serial reaction time tasks. In Experiment 1 with short response-stimulus intervals (RSI), we assume that there is no time to engage attention at the fixation cross before the onset of a new stimulus. In agreement with the hypothesis, Experiment 1 reveals no Simon effect when the stimulus location is repeated. In Experiment 2 with long RSI, we obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
122
3

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(136 citation statements)
references
References 34 publications
11
122
3
Order By: Relevance
“…A typical finding when investigating Simon compatibility effects, for example, is that the size of the Simon effect critically depends on the characteristics of the preceding trial. In particular, the sequential modulation effect reflects the finding that Simon effects in a current trial N are smaller following incompatible trials in N -1 compared to those following compatible trials in N -1 (Akçay & Hazeltine, 2007;Fischer, Dreisbach, & Goschke, 2008;Hommel, Proctor, & Vu, 2004;Notebaert, Soetens, & Melis, 2001;Stürmer, Leuthold, Soetens, Schröter, & Sommer, 2002;Wühr & Ansorge, 2005).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A typical finding when investigating Simon compatibility effects, for example, is that the size of the Simon effect critically depends on the characteristics of the preceding trial. In particular, the sequential modulation effect reflects the finding that Simon effects in a current trial N are smaller following incompatible trials in N -1 compared to those following compatible trials in N -1 (Akçay & Hazeltine, 2007;Fischer, Dreisbach, & Goschke, 2008;Hommel, Proctor, & Vu, 2004;Notebaert, Soetens, & Melis, 2001;Stürmer, Leuthold, Soetens, Schröter, & Sommer, 2002;Wühr & Ansorge, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…In binary choice tasks, such sequential modulation effects have often been explained in terms of bottom-up driven S-R feature repetitions and/or feature bindings (Hommel, 1998;Hommel et al, 2001Hommel et al, , 2004Nieuwenhuis, Stins, Posthuma, Polderman, Boomsma, & De Geus, 2006;Notebaert et al, 2001;Wendt, Kluwe, & Peters, 2006). 1 If a stimulus and the response to the stimulus co-occur in time, their features related to task-relevant stimulus or response dimensions are spontaneously integrated into a common event file comprising both stimulus-and response-related feature information such as form and position (Hommel et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The model that has the most support in the literature is the alternative-route model, where it is suggested that the effect is caused by the activation of a spatial code generated by the irrelevant spatial stimulus attribute (e.g., Kornblum, Hasbroucq, & Osman, 1990;Kornblum & Stevens, 2002). According to this model, when a stimulus dimension overlaps with a response dimension, features of the same stimulus can be processed along two different routes, a controlled route and an automatic responsepriming route (e.g., Hommel & Prinz, 1997;Notebaert, Soetens, & Melis, 2001). The controlled route follows the intentional translation of a stimulus attribute into response activation.…”
mentioning
confidence: 99%
“…Besides the modulatory influence of location-relevant practice, SEs can be eliminated (Notebaert & Soetens, 2003;Notebaert et al, 2001) and even reversed when the preceding trial in a serial task is incongruent (e.g., Mordkoff, 1998;Stürmer, Leuthold, Soetens, Schröter, & Sommer, 2002;Valle-Inclán, Hackley, & de Labra, 2002). In terms of the alternative-routes model, this effect was originally explained as the blocking (Stoffels, Van der Molen, & Keuss, 1989) or gating (Mordkoff, 1998) of the unconditional route by control processes.…”
mentioning
confidence: 99%
See 1 more Smart Citation